Subacute Thyroiditis – literature overview and COVID-19 - Domin, Remigiusz; Szczepanek-Parulska, Ewelina; Dadej, Daniela; Ruchała, Marek (Journal of Medical Science, 2020)
Subacute thyroiditis (SAT), also known as de Quervain’s thyroiditis, is a rare thyroid gland disorder, although it is the most common type of painful thyroiditis. The incidence of this disorder is relatively low but likely to be underestimated. Epidemiological studies vary, estimating a prevalence of 12/100,000/year and patients with SAT constitute less than 5% of all patient consultations due to thyroid disease. For the reason, that SAT can present with a variety of symptoms to different specialists. This review summarises current knowledge of SAT with an emphasis on reports related to SARS-CoV-2.